Proposta de ações de qualidade de vida no trabalho para a unidade universitária descentralizada da UFSM – Campus Frederico Westphalen - Bisognin, Adriane dos Santos Marques (2016)
The search for the development of the theme Quality of Life at Work as a key element in the management of any organization has been one of the targets for those seeking to promote innovation in management. Thus this research sought to understand what QVT actions may be proposed in the short, medium and long term for Servers UFSM Campus Frederick. For this we analyzed based on the biopsychosocial model and Organizational Limongi-France (1996), as QVT is being developed in the Federal Universities of Brazil; such universities were selected through the website of the Ministry of Education (MEC) and by similarity of their structures with the Dean of People UFSM Management. An analysis was also based on the same model of QVT, the actions developed by the Coordination of Health and Quality of Life UFSM through the site of UFSM and documents transferred by this Coordination. Finally, we identified the interest of servers, Campus Frederick, the actions proposed by CQVS by elaborate form, the author, Google-Drive, which allowed, through the answers, get a ranking of the actions that most arouse the interest of servers. With the information obtained in these different stages of the research is concluded that the most worked dimension in the country is organic, as appears in twelve of the thirteen universities selected; this dimension refers to the promotion of health, control of environmental risks and care for the physical needs in the workplace; the presence of this dimension was unanimous in the four regions of the country. It was also found that the UFSM promotes their actions directed more to the organizational dimension, ie for the training and qualification of its servers. Servers Campus Frederick, however, expressed equally divided interest between the social, biological and organizational, that is, beyond the previously highlighted the servers still interested in stocks that offer mandatory and spontaneous social benefits, which arouse collective values and recreational opportunities and culture. These results led the construction of a proposed action that has been divided into: short-term, given the need to use the Multiweb available in the institution, and the mobilization of the servers themselves; in the medium term, considering the need to develop projects and establish agreements and; longterm, due to the trading demand from servers at the center direction. This proposal opens the possibility of developing quality of life actions at work not only on campus Frederick as other units Decentralized University UFSM.